Uncovering the action mechanism of homoharringtonine against colorectal cancer by using network pharmacology and experimental evaluation. Issue 2 (20th December 2021) - Qu, Muwen; Li, Junyi; Yuan, Lingling
ABSTRACT: Homoharringtonine (HHT), an Food and Drug Administration (FDA)-approved anti-leukemia drug, exerts anti-tumor activity in several solid tumors, including colorectal cancer (CRC). However, its mechanism of action in CRC progression has not been comprehensively elucidated. The drug-disease targets were obtained using publicly available databases. Protein–protein interaction (PPI) network, Gene ontology (GO) function and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway enrichment were performed to reveal the core targets, biological processes and signaling pathways of HHT against CRC. Cell and animal experiments were performed to validate the inhibitory effects of HHT on CRC. A total of 98 overlapping target genes of HHT and CRC were predicted. Through PPI network and topology analysis, we screened out 23 hub genes. Enrichment assays showed 163 biological processes (BP), 18 cell components (CC), 35 molecular functions (MF), and 85 related pathways. Functionally, HHT inhibited CRC cell proliferation, cell cycle progression, colony formation, migration and invasion, and promoted apoptosis. HHT treatment resulted in the inactivation of PI3K/AKT/mTOR signaling in CRC cells. Moreover, activation of PI3K/AKT/mTOR signaling by 740Y-P abated the suppressive effects of HHT on cell malignant phenotypes. Furthermore, HHT repressed CRC tumor growth in nude mice. Our current study demonstrated that HHT repressed CRC progression at least partly by inactivating PI3K/AKT/mTOR signaling pathways, highlighting HHT as a potential therapeutic agent for CRC patients.